Strategies for managing endowment funds : case studies of selected Malaysian public universities - Nurul Adilah Hasbullah,; Asmak Ab Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Malaysian government has strongly encouraged Malaysia’s public universities to seek additional sources of income to assure the sustainability of their finances. Endowment is one of the sources encouraged by the government for implementation by these universities. This encouragement has received a positive response from public universities: all of them have now implemented endowment funds. However, the strategies used by these institutions in managing these funds are still poorly documented. Therefore, this study was conducted to explore the strategies used by Malaysian public universities in managing such funds. It is a qualitative study conducted by interviewing six representatives from selected public universities: Universiti Malaya (UM), Universiti Kebangsaan Malaysia (UKM) and Universiti Teknologi Malaysia (UTM). These public universities were selected because they recorded the highest collection of endowment funds. This study found that the strategies in managing endowment funds in Malaysian public universities include diversified investment portfolios, the appointment of investment experts, Shariah-compliant investments as an alternative, and diversified income sources.